DETERMINAN STIGMA INTERNAL PADA CAREGIVER ANAK BERKEBUTUHAN KHUSUS (ABK) DI SLB ABC KABUPATEN BOGOR - Tiara, Intan Dwi; Pratiwi, Rita Dwi; Alita, Dini Arum; Fadhilah, Humaira (Edu Dharma Journal :Jurnal penelitian dan pengabdian masyarakat, 2025)
ABSTRACTAccording to WHO (2020), Internal stigma is people being labeled, stereotyped, and discriminated against because they are associated with a disease. Based on data from the Central Statistics Agency (BPS) (2019), the number of people with disabilities in Bogor Regency reached 7,358, of which 1,025 were children. The purpose of the study was to find out the factors that affect the occurrence of internal stigma in  ABK caregivers at SLB ABC Tunas Kasih 1 Leuwiliang, Bogor Regency. This research method is quantitative research and uses a cross-sectional study design research method, with a sample of 52 respondents. Data analysis in bivariate analysis using the chi-square test and multivariate analysis using the logistics binary test. The results of the study showed that the results of the statistical test showed that there was a relationship between knowledge and internal stigma (p-value 0.040), there was a relationship between perception and internal stigma (p-value 0.001), there was no relationship between resilience and internal stigma (p-value 0.103), there was no relationship between family burden and internal stigma (p-value 0.873), there was a relationship between quality of life and internal stigma (p-value 0.021). In conclusion, knowledge and perception are the most influential factors in the occurrence of internal stigma in caregivers of children with special needs (ABK) at SLB ABC Tunas Kasih 1 Leuwiliang Bogor Regency because it has a p-value0.05. The advice can add insight and knowledge to parents about what factors can affect the internal stigma on them as  ABK caregivers so that caregivers can reduce the internal stigma they have.                                               ABSTRAKMenurut WHO (2020), internal stigma adalah orang diberi label, stereotip dan didiskriminasi karena dikaitkan dengan suatu penyakit. Berdasarkan data Badan Pusat Statistik (BPS) (2019), jumlah penyandang disabilitas di Kabupaten Bogor mencapai 7.358, dimana 1.025 adalah anak-anak. Tujuan penelitian untuk mengetahui faktor-faktor yang mempengaruhi terjadinya stigma internal pada caregiver ABK di SLB ABC Tunas Kasih 1 Leuwiliang Kabupaten Bogor. Metode penelitian kuantitatif dengan desain studi cross-sectional, jumlah sampel sebanyak 52 responden. Analisis data dalam analisis bivariat menggunakan uji chi-square dan analisis multivariat menggunakan uji binary logistik. Hasil uji statistik menunjukkan bahwa terdapat hubungan antara pengetahuan dengan stigma internal (p-value 0,040), terdapat hubungan antara persepsi dengan stigma internal (p-value 0,001), tidak terdapat hubungan antara resiliensi dengan stigma internal (p-value 0,103), tidak terdapat hubungan antara beban keluarga dengan stigma internal (p-value 0,873), terdapat hubungan antara quality of life dengan stigma internal (p-value 0,021). Kesimpulan pengetahuan dan persepsi merupakan faktor yang paling berpengaruh terhadap terjadinya stigma internal pada caregiver anak berkebutuhan khusus (ABK) di SLB ABC Tunas Kasih 1 Leuwiliang Kabupaten Bogor karena memiliki nilai p-value0,05. Saran dapat menambah wawasan dan pengetahuan kepada orang tua tentang faktor-faktor apa saja yang dapat mempengaruhi stigma internal pada mereka sebagai caregiver ABK sehingga caregiver dapat mengurangi stigma internal yang mereka miliki.